2007
DOI: 10.1007/s00233-007-0731-9
|View full text |Cite
|
Sign up to set email alerts
|

Generating Self-Map Monoids of Infinite Sets

Abstract: Let Ω be a countably infinite set, S = Sym(Ω) the group of permutations of Ω, and E = Self(Ω) the monoid of self-maps of Ω. Given two subgroups G 1 , G 2 ⊆ S, let us write G 1 ≈ S G 2 if there exists a finite subset U ⊆ S such that the groups generated by G 1 ∪ U and G 2 ∪ U are equal. Bergman and Shelah showed that the subgroups which are closed in the function topology on S fall into exactly four equivalence classes with respect to ≈ S . Letting ≈ denote the obvious analog of ≈ S for submonoids of E, we prov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Mesyan [19,Proposition 4] proved that cf(Self(Ω)) > ℵ 0 using an elementary diagonal argument, and an alternative proof of Theorem 4.1 can be obtained using a similar argument. In Galvin [11] it was shown that the symmetric group on an infinite set is strongly distorted.…”
Section: Positive Examplesmentioning
confidence: 99%
“…Mesyan [19,Proposition 4] proved that cf(Self(Ω)) > ℵ 0 using an elementary diagonal argument, and an alternative proof of Theorem 4.1 can be obtained using a similar argument. In Galvin [11] it was shown that the symmetric group on an infinite set is strongly distorted.…”
Section: Positive Examplesmentioning
confidence: 99%
“…This equivalence relation and the results of this section are modeled on those in [2], where Bergman and Shelah define an analogous relation for groups and classify into equivalence classes the subgroups of the group of permutations of a countably infinite set that are closed in the function topology. Properties of such an equivalence relation defined for submonoids of the monoid of self-maps of an infinite set are investigated in [8].…”
Section: Equivalence Classesmentioning
confidence: 99%
“…In [10] it was proved that contains at least two incomparable elements by constructing a subsemigroup S of N N such that S F 3 and F 3 S. In Section 4 we gave an example of a subsemigroup incomparable to all F n . The following theorem shows that there are anti-chains in of arbitrary finite length.…”
Section: Anti-chainsmentioning
confidence: 99%